American and European relations with China: Advancing common agendas - David Shambaugh; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2008)
This volume is the collaborative product of American and European specialists on China, a number of whom have been involved in transatlantic consultations concerning China over the years. With generous support of the German Marshall Fund of the United States, the German Institute for International and Security Affairs (SWP), and the China Policy Program of the Elliott School of International Affairs at George Washington University, the contributors to this volume were joined by more than a dozen other European specialists on Chinese affairs and U.S.-Europe relations for a stimulating two-day conference at the SWP in Berlin on 21-22 February 2008. The discussions were rich, candid, and detailed. The conference agenda, and the organization of this volume were intentionally structured around parallel American and European papers on six topics (the "Big Picture" of China's reform and opening, Chinese domestic issues, security issues, economic issues, and foreign policy issues), so as to clearly expose both similarities and differences in transatlantic perspectives and policies.While certain differences were apparent, the commonalities that emerged in the papers and discussions far outweighed the differences. This fact confirmed the conference organizers' previous sense that transatlantic differences concerning China had been substantially narrowed in recent years and, as a result, that a new window had opened for transatlantic cooperation vis-à-vis China. This is encouraging news, both for transatlantic relations but also because so many global challenges in today's world require common cooperation not only across the Atlantic but trilaterally among China, Europe, and the United States
Keywords: 320